THE VUCA CONCEPT IN THE DIGITAL SPHERE - Simona-Valentina Pașcalau (Agora International Journal of Economical Sciences (AIJES), 2023)
The article's main goal is to explain the idea of VUCA in detail and show how it may affect digital marketing efforts. The article's goal is to give those interested skills and strategies to deal with the difficulties and uncertainties in a constantly evolving digital world by examining the idea of VUCA in the context of digital marketing. It will examine how decision-making in digital marketing can be influenced by elements including volatility, uncertainty, complexity, and ambiguity and how these factors can be effectively controlled. The article's main objective is to inform about the significance and influence of the VUCA concept in the digital sphere and to offer helpful advice for adjusting to and thriving in a digital marketing environment.
Keywords: 330